Does the shadow economy explain household saving? - Oinonen Sami; Viren Matti (SUERF - The European Money and Finance Forum, 2026)
We analyze the question of how indicators of shadow economy correspond to the National Accounts values starting with the notion that shadow economy should show up in the difference between household income and consumption in the sense that household (disposable) income is underreported. By contrast, household consumption is more accurate because most of shadow economy income eventually ends up to consumption. Thus, household saving figures should be negatively related to the values of shadow economy: if these values are large, savings should be small, or even negative and vice versa. We test this hypothesis with European cross-country data for 1991-2017 using the so-called MIMIC model calculations as point of reference. Estimation results lend very little support to this hypothesis even though we can otherwise explain pretty well the cross-country variation in household saving and consumption growth rates.